2012
DOI: 10.1111/j.1439-0531.2009.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Donor Age on the Developmental Competence of Bovine Oocytes Retrieved by Ovum Pick Up

Abstract: To study the effect of donor age on oocyte developmental competence and steroid profiles, the crossbred cow (Murray Grey × Brahman) in Yunnan province of China were selected and divided into three groups according to its age. The three groups were young cows (n = 12; 12 months old), middle-aged cows (n = 15; parity: ≤3 calvings; age: 7-8 years old) and old cows (n = 10; parity: ≥8 calvings; age: ≥15 years old). Cumulus-oocyte complexes (COCs) were collected by 10 consecutive ovum pick up (OPU) sessions with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
4
21
2
2
Order By: Relevance
“…There were more COCs (71) collected in Group I than in Group 2 cows with 29 COCs. The same trend was observed where Su et al (2009) aspirated fewer follicles and obtained lower COC numbers in old cows than in middle-aged and young cows. The collected COCs from Group I were classified into rank A, 5.63% (n=4) with intact 3 layers cumulus cells, rank B, 2.82% (n=2) with uneven dark ooplasm but had 3 layers intact cumulus cells, rank C, 32.39% (n=23) homogenously dark granulation of ooplasm and with intact/compact, 1 to 2 layers cumulus cells and rank D, 59.15% (n=42) without cumulus cells.…”
Section: Resultssupporting
confidence: 67%
“…There were more COCs (71) collected in Group I than in Group 2 cows with 29 COCs. The same trend was observed where Su et al (2009) aspirated fewer follicles and obtained lower COC numbers in old cows than in middle-aged and young cows. The collected COCs from Group I were classified into rank A, 5.63% (n=4) with intact 3 layers cumulus cells, rank B, 2.82% (n=2) with uneven dark ooplasm but had 3 layers intact cumulus cells, rank C, 32.39% (n=23) homogenously dark granulation of ooplasm and with intact/compact, 1 to 2 layers cumulus cells and rank D, 59.15% (n=42) without cumulus cells.…”
Section: Resultssupporting
confidence: 67%
“…A decrease in cleavage rate as well as blastocyst formation rate, following IVF, was observed in COCs retrieved by OPU from old cows (>15 years age) in comparison to middle-aged and young cows in a recent study conducted by Su et al (2012). The present study revealed that expression of various genes involved in developmental competence of oocytes is directly related to their quality, vis-a-vis morphological appearance of the retrieved COCs.…”
Section: Discussionsupporting
confidence: 59%
“…Though the linking of this oocyte retrieval approach with in vitro embryo production proved to be a valuable new development in cattle breeding and embryo transfer industry (Duszewska and Reklewski, 2000), the variation in the quality of recovered oocytes and their developmental potential remains a major concern. This variation in oocyte quality might be attributed to OPU devices such as needle (Bols et al, 1996 and and negative aspiration pressure (Bols et al, 1996 and that are used for oocyte retrieval, in addition to major animal effect (if any) such as age which has been shown to bear a considerable effect on both cleavage and blastocyst formation rates (Su et al, 2012). Since, morphological grading system, based on cumulus-oocyte complexes (COCs) aspirated from slaughter house obtained ovaries, seems ambiguous in OPU retrieved oocytes, owing to their harsher retrieval as compared with the follicular aspiration (Bols et al, 2012;Merton et al, 2013), the relative expression of various genes associated with cumulus-oocyte interaction, fertilization, genome reprogramming and development would serve as an important criterion to do the same irrespective of, or in addition to, the morphological appearance of the COCs.…”
Section: Introductionmentioning
confidence: 99%
“…HCP 4 during the periestrus phase can also impair the reorganization of mitochondria and cortical granules during bovine oocyte maturation with possible negative effects on developmental competence. Accordingly, oocytes collected from cows with HCP 4 showed a reduction in cleavage and blastocyst formation in vitro (Su et al 2009). Moreover, apoptosis of canine cumulus-oocyte complexes was associated either with low or high serum P 4 concentrations ), indicating the importance of keeping a physiological range for normal oocyte function.…”
Section: Discussionmentioning
confidence: 97%